Heat transfer characteristics and internal fluidity of a sessile droplet on hydrophilic and hydrophobic surfaces. (5th September 2016) - Al-Sharafi, Abdullah; Yilbas, Bekir S.; Sahin, Ahmet Z.; Ali, Haider; Al-Qahtani, H.
Highlights: Heat transfer from direction modifies rotation of circulation cells in droplet. Marangoni flow current is dominant inside droplet. Nusselt number increases when heat transfer occurs from substrate surface to droplet. Nusselt number attains higher values for hydrophobic surface than hydrophilic surface. New number introduced combines the Bond number and interfacial surface energies. Abstract: Heat transfer characteristics for a sessile droplet are examined for various droplet contact angles resembling hydrophilic and hydrophobic characteristics of the surface. In the heat transfer analysis, two cases are considered including heat transfer from droplet to the substrate surface (case 1) and heat transfer from the substrate surface to the droplet (case 2). Temperature and flow fields inside the droplet are simulated and velocity predictions are validated through the experimental data. Variation of the Nusselt and the Bond numbers with the droplet contact angle is analyzed for two heating situations (case 1 and case 2). The findings revealed that two counter rotating circulation cells are formed inside the droplet for the case of hydrophilic surface characteristics. The number of circulation cells increases to four for the case of hydrophobic surface characteristics. This behavior is attributed to the combine effect of the Marangoni and the buoyancy forces on the flow field. Rotational direction of the circulation cells changes with the heat transfer direction (case 1 and case 2) and the Nusselt number attains higher values for the case of heat transfer from substrate surface towards the droplet. The Nusselt and the Bond numbers demonstrates increasing trend with increasing the droplet contact angle, which is more pronounced for the high droplet contact angles. The Bond number and the droplet contact angle are correlated into a new number, Ayse number, which demonstrates a linear variation with the Nusselt number.